Implementation of Ventilator Associated Pneumonia (VAP) Prevention in Health Care and Its Effectiveness: Literature Review - Mugi Rahayu Lestari; Bunga Andriana; Solita Claudya Aguilera; Chandrayani Simanjorang; Riswandy Wasir; Apriningsih Apriningsih (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: The incidence of HAIs in developed countries is estimated at around 1/100 hospitalized patients, while in developing countries it is around 10/100 patients. Patients receiving mechanical ventilation accounted for 86% of HAI cases. As many as 9-27% of patients with ventilator installation have the possibility of suffering from VAP. Objectives: This study aims to describe the implementation of VAP prevention and its effectiveness in health care services. Research Metodes: This type of research is literature study through the search engines ScienceDirect, Google Scholar, and PubMed. Results: Of the thirteen articles obtained, there were six articles discussing the implementation of VAP prevention in health services, six articles discussing the effectiveness of VAP prevention in health services, and one article discussing both. Conclusion: Prevention of VAP in health services is carried out through surveillance and bundles. This prevention is very effective in reducing VAP cases in health care facilities if the implementation is optimal